Hambatan Kesiapan Masyarakat Desa Sei Ahas dalam Pembangunan Canal Blocking pada Rawa Gambut - Wijaya, Ellias (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
Peatland condition in Central Kalimantan is severely damaged after the initiation of one million hectare peatland project. An attempt to restore the peatland condition by the Ministry of Public Work is by making dam to maintain water flow and water tabel. The plan of building such dam in Sei Ahas village, Central Kalimantan turns out facing social constraints that strongly related to community readiness level. Considering the importance of blockings in supporting the restoration of peatland ecosystem, it is deemed necessary to examine what aspects hampering community readiness in accepting and utilizing the dams. This research is conducted in Sei Ahas village in 2013 using integratif research approach. Data are collected through indepth interview, survey, field observation, and literature studies. The community readiness level is categorized as preplanning. Factors that impede the Sei Ahas community readiness are concerns on the disruption of their livelihood, community’s low understanding on carbon emission and peatland fire, wrong perception against dam’s functions and mechanisms, and the unharmonious social network of the society.